Interactions of equatorial winds in super-Eddington stellar sources - Abaroa, Leandro (2021)
Compact objects accreting at super-Eddington rates launch powerful winds and jets. The jet interacts with the wind of the disk. A powerful jet pushes the wind sidewards producing a supersonic equatorial outflow. Such a situation might be the case in the well-known super-accreting Galactic microquasar SS433, where the existence of an equatorial wind has been revealed by high-resolution radio observations. In this work, we present preliminary results of quantitative estimates of the expected radiation from the interaction between a jet-induced equatorial wind and a very luminous donor star with weak or null winds (e.g. a PopIII star). The results are of interest for understanding ultraluminous X-ray sources and other super-Eddington accretors in the early universe.